Military masculinity and postwar recovery in the Soviet Union - Fraser, Erica L. 1976- (University of Toronto Press, 2019)
"Catastrophic wartime casualties and postwar discomfort with the successes of women who had served in combat roles combined to shatter prewar ideals about what service meant for Soviet masculine identity. The soldier had to be re-imagined and resold to a public that had just emerged from the Second World War, and a younger generation suspicious of state control. In doing so, Soviet military culture wrote women out and attempted to re-establish soldiering as the premier form of masculinity in society. Military Masculinity combines textual and visual analysis, as well as archival research to highlight the multiple narratives that contributed to rebuilding military identities. Each chapter visits a particular site of this reconstruction, including debates about conscription and evasion, appropriate role models for cadets, misogynist military imagery in cartoons, the fraught militarized workplaces of nuclear physicists, and the first cohort of cosmonauts, who represented the completion of the project to rebuild militarized masculinity."--